PERANCANGAN UI/UX MENGGUNAKAN METODE TASK CENTERED SYSTEM DESIGN DAN USER EXPERIENCE QUESTIONNAIRE pada WEBSITE banyumaskab.go.id - Fatma, Oktiara Anggita (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
The development of information and communication technology is growing rapidly in the dissemination of website-based information. The banyumaskab.go.id website is a government website that provides public information services. However, the appearance of the banyumaskab.go.id website is less attractive, the information is not updated enough, there are still empty menus such as tourist menus, hotels, regulations, transportation, news, articles, announcements, guest books, galleries and videos. homepage, Banyumas, getting to know Banyumas, local government, Important Banyumas, media center, galelri Banyumas, public menu.. To solve problems using the Task Centered System Design and User Experience Questionnaire methods. Task Centered System Design as a problem solving method in creating a user interface plan that can meet task needs and user needs. Meanwhile, the User Experience Questionnaire is a tool in the form of a questionnaire. The results of this research are the design of a new design for the banyumaskab.go.id website with a prototype, and the average value of each scale for improving the website has values of attractiveness, perspicuity, efficiency, precision (dependability), simulation (stimulation), novelty (novelty) demonstrated at a level above average. Keywords: Design, Government, User Experience Questionnaire, Task Centered System Design, Website.